Comparison of obesity based on various obesity indices in metabolic dysfunction-associated fatty liver disease (MAFLD) subjects: A comparative analysis of anthropometric and bioimpedance indices - Hamid, Widya Inarah Nadhilah; Aman, Andi Makbul; Rasyid, Haerani; Bakri, Syakib; Daud, Nu'man As; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a terminology that describes the condition of fatty liver accompanied by metabolic disorders. Previous studies have shown obesity is associated with MAFLD, but fatty liver can also be observed in non-obese individuals. The obesity measurement index can reflect obesity levels and can be used as a screening tool for metabolic diseases such as MAFLD. In addition to Body Mass Index (BMI), there are several other measurement indices, such as Waist Circumference (WC), Waist-to-Height Ratio (WHtR), as well as Body Fat Percentage (BF%) and Fat Mass Index (FMI). This study aims to see the comparison of obesity prevalence in MAFLD patients based on various measurement indices. Methods: This study was conducted at Wahidin Sudirohusodo Hospital in Makassar, Indonesia, using an observational study with a cross-sectional design. The various obesity indices were performed once the patient was newly diagnosed with MAFLD. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25.0. Results: This study consisted of 44 males (57.9%) and 32 females (42.1%), with an average age 41.8 years. The prevalence of obesity based on various indices in MAFLD subjects was as follows: WHtR (100%), LP (88.2%), FMI (86.8%), BF% (86.8%), and BMI (80.3%). Conclusions: The prevalence of obesity in MAFLD subjects was highest when measured by the WHtR index, followed by WC, FMI, BF%, and lowest when measured by BMI.